ENGLISH-INDONESIAN TRANSLATION METHOD AND QUALITY OF INTERROGATIVE SENTENCE IN THE “HARVEST MOON: BACK TO NATURE” VIDEO GAME - Nurul Intan Sari; Muhammad Yudha Setyagalam (Musamus Journal of Language and Literature, 2020)
This research focuses on translation method and the impact of translation method toward translation quality of interrogative sentence in the Harvest Moon: Back to Nature video game. Descriptive qualitative method is applied in this research. The data are the interrogative sentences found in the Harvest Moon: Back to Nature video game and its translation. The source data are the video game entitled Harvest Moon: Back to Nature developed by Victor Interactive Software, published by Natsume and its translation by PALAPA. The results of the research show that there are 4 methods applied to the translation namely Communicative Translation, Literal Translation, Free Translation, and Word-for-Word Translation. From 71 data of interrogative sentence in Harvest Moon: Back to Nature video game, the dominant translation method used is Communicative Translation with 36 data (50.7%). For the translation quality. From 71 data, 53 data categorized as accurate translation (74.6%), 60 data categorized as acceptable translation (84.5%), and 68 data categorized as readable translation (95.8%). The translation methods applied in translating interrogative in the video game can produce good quality translation.